2021
DOI: 10.52547/jcbior.2.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Detecting of biofilm formation in the clinical isolates of Pseudomonas aeruginosa and Escherichia coli: an evaluation of different screening methods

Abstract: Biofilm producer bacteria cause nosocomial, chronic, and recurrent human infections. It is hard to treat biofilm-embedded bacteria because they are more resistant to antimicrobials than planktonic bacteria. The present study aimed to investigate different methods for detecting biofilms in the clinical isolates of Escherichia coli and Pseudomonas aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…3), while non-membrane-forming E. coli isolates were found to be bright pink, red, or winecolored colonies. Mohsenzadeh et al (2021) noted that out of 100 E. coli and P. aeruginosa isolates, 38 (38 %) demonstrated a biofilm-positive phenotype under optimum circumstances in MTPA and isolates were further categorised as strong, moderate, weak, and no biofilm on Congo red agar The present study showed the number of UPEC that formed biofilm in vitro was 71%, which was comparable to the studies that were carried out by previous studies of Subramanian et al…”
Section: Detection Of Biofilm Formation By Congo Red Agar (Cra)supporting
confidence: 89%
“…3), while non-membrane-forming E. coli isolates were found to be bright pink, red, or winecolored colonies. Mohsenzadeh et al (2021) noted that out of 100 E. coli and P. aeruginosa isolates, 38 (38 %) demonstrated a biofilm-positive phenotype under optimum circumstances in MTPA and isolates were further categorised as strong, moderate, weak, and no biofilm on Congo red agar The present study showed the number of UPEC that formed biofilm in vitro was 71%, which was comparable to the studies that were carried out by previous studies of Subramanian et al…”
Section: Detection Of Biofilm Formation By Congo Red Agar (Cra)supporting
confidence: 89%
“…Biofi lm production is recognized as a contributing factor to the development of resistance in P. aeruginosa. Th e presence of biofi lm serves as a formidable obstacle for both the immune system and antibiotics, thus constituting a primary etiological factor in the development and progression of infectious diseases (Mohsenzadeh et al, 2021). Th e formation of a mucous layer and utilization of host proteins by biofi lm contribute signifi cantly to pathogenicity.…”
Section: Results P Aeruginosa Was Identifi Ed In 83mentioning
confidence: 99%
“…The TiO 2 /CIP and TiO 2 /CIP/Cs were the most effective samples for preventing biofilm formation, whereas TiO 2 was the least effective, showing no inhibition at the highest tested concentration (64 μg/mL) ( Figure 10 ). Biofilm production strength was classified based on the optical density (OD) of the isolate: ≤0.232 for no biofilm detected, 0.232 < OD isolate ≤ 0.464 for weak biofilm formation, 0.464 < OD isolate ≤ 0.929 for moderate biofilm formation, and OD isolate > 0.929 for strong biofilm formation [ 50 ]. To compensate for background absorbance, the OD reading value (570 nm) of the blank was deducted from the sample values.…”
Section: Resultsmentioning
confidence: 99%